Increased Alpha Band Functional Connectivity Following the Quadrato Motor Training: A Longitudinal Study - Lasaponara, Stefano; Mauro, Federica; Carducci, Filippo; Paoletti, Patrizio; Tombini, Mario; Quattrocchi, Carlo C.; Mallio, Carlo A.; Errante, Yuri; Scarciolla, Laura; Ben-Soussan, Tal D. (Frontiers in Human Neuroscience, 2017)
Quadrato Motor Training (QMT) is a new training paradigm, which was found to increase cognitive flexibility, creativity and spatial cognition. In addition, QMT was reported to enhance inter- and intra-hemispheric alpha coherence as well as fractional anisotropy in a numbers of white matters pathways including corpus callosum. Taken together, these results seem to suggest that electrophysiological and structural changes induced by QMT may be due to an enhanced interplay and communication of the different brain areas within and between the right and the left hemisphere. In order to test this hypothesis using the exact low-resolution brain electromagnetic tomography (eLORETA), we estimated the current neural density and lagged linear connectivity of the alpha band in the resting state electroencephalography (rsEEG) recorded with open and closed eyes at three different time points, following 6 and 12 weeks of daily QMT. Significant changes were observed for the functional connectivity. In particular, we found that limbic and fronto-temporal alpha connectivity in the open eyes condition increased after 6 weeks, while it enhanced at the closed eyes condition in occipital network following 12-weeks of daily training. These findings seem to show that the QMT may have dissociable long-term effects on the functional connectivity depending on the different ways of recording rsEEG. Open eyes recording pointed out a faster onset of Linear Lag Connectivity modulations that tend to decay as quickly, while closed eyes recording showed sensible effect only after the complete 3-months training.